Maximizing spring wheat productivity in the eastern Canadian Prairies: I. Yield, yield components, and lodging risk. (13th May 2022) - Mangin, Amy; Brûlé‐Babel, Anita; Flaten, Don; Wiersma, Jochum; Lawley, Yvonne
Abstract: Spring wheat ( Triticum aestivum L.) yields across the Canadian prairies are rising, however, a yield gap remains between average yield and yield potential, which can be explored further under Prairie conditions. The high rates of nitrogen (N) fertilizer required for current high‐yielding cultivars may increase lodging risk adding to this yield gap. The objectives of this study were to determine the influence of intensive management through N fertilization and plant growth regulator (PGR) application, on grain yield, yield components, and their relationships, in addition to lodging risk. Field trials were conducted at two locations in 2018 and 2019 in Manitoba, Canada, to evaluate three high‐yielding spring wheat cultivars, three N management strategies, and the application of a PGR. Kernels per spike had the strongest overall linear relationship with grain yield ( r 2 = .47), while the response of spikes per plant was highly related to yield response with alterations in N and PGR management practices ( r 2 = .98). Splitting N fertilizer applications showed potential to reduce lodging risk of spring wheat, while maintaining yield and increasing protein. The PGR applications reduced lodging and increased grain yield by 91 kg ha −1 mainly through increases in kernels per spike. To achieve consistent yield increases, management practices should maximize early season N availability to target increases in spikes per plant and kernels per spike, thus a PGR application may be required to balance increased lodging risk. Core Ideas: Split N application timings maintained yield, reducing lodging risk, and increasing protein content. Plant growth regulator increased yield in the absence of lodging by increasing the number of kernels per spike. Grain yield response to management changes was highly dependent on changes in spikes per plant. Plant growth regulator has the ability to reduce lodging risk when high N rates are applied at planting.